From spontaneous order to induced disorder: Neoliberalism and subsidiarity of the State - Campodónico Sánchez, Humberto (2020)
The history of economic thought in the 20thcentury gave rise to a series of important discussions that have guided economic politics and geopolitical relations in most countries in the world. The criticism to the tenets of classical economy would originate a number of proposals that lay down significant reforms. This article describes and analyzes the proposals of two schools that justly confront classical thought. The first one belonging to John Maynard Keynes questions the “natural” order of economic laws and suggests a key intervention of the State in their regulation. The second one is that of Friedrich Hayek, which would lay the foundations of neoliberalism, based on a fundamental economic freedom (even above political freedom) and an intervention of the State in it. The article concludes with an analysis of the economic politics in Chile and Peru, countries that illustrate the ultimately development of a neoliberal model in the last decades.